2011
DOI: 10.1021/ar200053d
|View full text |Cite
|
Sign up to set email alerts
|

From α-Arylation of Olefins to Acylation with Aldehydes: A Journey in Regiocontrol of the Heck Reaction

Abstract: The Pd-catalyzed Mizoroki-Heck reaction of olefins with aryl halides, more often simply called the Heck reaction, was recently recognized with the 2010 Nobel Prize in chemistry. Although highly selective with electron-deficient olefins, which generally yield the linear β-arylated product exclusively, the Heck reaction is less satisfactory with electron-rich olefins. This substrate typically generates a mixture of both α- and β-arylated regioisomeric products, hampering wider application of the reaction in chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
72
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(72 citation statements)
references
References 68 publications
0
72
0
Order By: Relevance
“…have been deployed for the C H activation reactions. The aldehyde C H activation by direct acylation of aryl halides with aliphatic aldehydes is an interesting prospect to get alkyl-aryl ketones; which are potential intermediates in different pharmaceutical, fragrance, dye and agrochemical industries [14][15][16][17][18][19][20][21][22]. Friedel-Crafts acylation has been a traditional way of acylating arenes, which has the strict limitation of reacting with activated benzene derivatives only [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been deployed for the C H activation reactions. The aldehyde C H activation by direct acylation of aryl halides with aliphatic aldehydes is an interesting prospect to get alkyl-aryl ketones; which are potential intermediates in different pharmaceutical, fragrance, dye and agrochemical industries [14][15][16][17][18][19][20][21][22]. Friedel-Crafts acylation has been a traditional way of acylating arenes, which has the strict limitation of reacting with activated benzene derivatives only [23].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of alkyl-aryl ketones by direct acylation of aryl halides with aliphatic aldehydes have been reported by using palladium complexes of phosphine ligands as well as palladium nanopaticles [16][17][18][19][20][21]. Selection of ligands plays an important role in determining the efficiency of the catalysts for generating the Pd(0) species for the reaction cycle to start.…”
Section: Introductionmentioning
confidence: 99%
“…However, the major drawback of the Mizoroki–Heck-type reaction in the synthesis of 1,1-disubstituted olefins rests on its poor selectivity toward the formation of α-products [2023]. In general, the reaction shows β-selectivity, and there are only a few reports available concerned with α-substituted products [2426]. Sabarre and Love reported a one-pot rhodium-catalyzed alkyne hydrothiolation followed by a nickel-catalyzed Kumada-type cross coupling with Grignard reagents to afford 1,1-disubstituted olefins [27].…”
Section: Introductionmentioning
confidence: 99%
“…[16] We found that both R 3 NH + salts and glycol were needed in our study of the asymmetric Heck reaction of aryl halides. [17] In our DFT studies, hydrogen bonding of trialkylammonium NH and alcoholic ROH with a halide ion not only lowered the barrier, but also stabilized the ionized products.…”
mentioning
confidence: 96%